Characteristics of Rotary Electromagnet with Large Tooth-pitch Angle - Meng Bin; Ruan Jian; Li Sheng (Institute of Advanced Engineering and Science, 2012)
Since the conventional electro-mechanical converter of 2D valve had problems of step lose due to its small tooth-pitch angle, a novel rotary electromagnet with large tooth-pitch angle and coreless rotor structure was proposed. Combined with the approaches of magnetic circuit analysis, finite element simulation and experimental study, the static and dynamic characteristics of electromagnet including torque-angle characteristics, frequency response and step response were studied. The experimental results are in a close agreement with the simulated results. The electromagnet has sinusoidal torque-angle characteristics and good dynamic response. The maximum static torque is approximately 0.083N.M, and its frequency width is about 125Hz/-3dB, 130Hz/-90°, respectively, and the rise time is about 5.5 ms. It is appropriate to be used as the electro-mechanical converter of 2D proportional valve. DOI:http://dx.doi.org/10.11591/telkomnika.v10i6.1446